Efficacy of potential atypical antipsychotic lek-8829 on behavioral effects in rat model of catalepsy and inhibition of amphetamine induced psychomotor stimulation - Bogićević, Sanja (Slovenian veterinary research, 2015)
D2 antagonist drugs, such as haloperidol, are potent antipsychotic drugs but unfortunately also have a high propensity to cause unwanted extrapyramidal syndrome (EPS). LEK-8829 is a dopamine D2 receptor antagonist with intrinsic activity at dopamine D1 receptors. Here we speculate that the intrinsic activity of LEK-8829 at dopamine D1 receptors may reduce its propensity to provoke EPS. The experimental rats were thus behaviorally evaluated in sessions performed before and after the 21 day treatment period with haloperidol or LEK-8829, for the induction of catalepsy or for the inhibition of amphetamine-induced locomotor activity in the open field by the same dose of the respective drug as was used for 21 daily injections. We found that after 21 day treatment with LEK-8829 or haloperidol, both drugs retained or even increased their potential for the induction of catalepsy. However, while LEK-8829 retained its efficacy for the inhibition of amphetamine-induced psychomotor stimulation, the efficacy of haloperidol was significantly diminished. We conclude that LEK-8829 retains its antipsychotic efficacy during prolonged treatment and possess lower propensity for the induction of EPS as compared to typical neuroleptic haloperidol.
Keywords: LEK-8829; antipsihotiki; dopamine D1 agonist; dopamine D2 antagonist; dopaminski agonist D1; dopaminski antagonist D2